Effect of digestion on the phenolic content and antioxidant activity of celery leaf and the antioxidant mechanism via Nrf2/HO‐1 signaling pathways against Dexamethasone. Issue 7 (17th May 2019) - Han, Liying; Gao, Xiaoxiao; Xia, Ting; Zhang, Xueqian; Li, Xia; Gao, Wenyuan
Abstract: The effect of digestion on the phenolic compounds and antioxidant activity of celery leaf were performed. In this work, 13 phenolic chemicals were discriminated by HPLC‐MS, and content of phenolic and the antioxidant capacity were evaluated after digestion in vitro. After digestion, the content of phenols and flavonoids were increased by about 3–6‐folds correlated with the average antioxidant activity ( p < 0.05). It was found that the extraction of celery leaf (ET) decreased lipid peroxidation (MDA) and reactive oxygen species (ROS) level, and elevated the antioxidant activities of the liver, spleen, and thymus in Dexamethasone (Dex)‐treated KM mice. Furthermore, ET increased the protein transcription of NF‐E2‐related factor 2 (Nrf2), hemeoxygenase‐1 (HO‐1) and glutathione s‐transferase (GST) to against oxidation. These results suggested that ET can protect animals through the Nrf2/HO‐1 signaling pathway from oxidative damage included by Dex. Practical applications: Celery is a daily edible vegetable with more pharmacological research focused on dietary fiber, yet fewer studies on the biological activity of small molecules, especially that in leaves. This study shows that the phenolic compounds from celery leaf have a distinct enhancement of oxidation after digestion in vitro, and the celery leaf reduces oxidative stress induced by Dex via Nrf2/HO‐1 signaling pathway, indicating celery leaf or other food rich in phenolic compounds can be good source of functional food to fully use to promote the economic value. Moreover, it also provides theoretical information of celery leaf on digestion, which insinuates that food or Chinese medicine containing flavonoids, such as glycoside of apigenin or luteolin, have the similar digestion pattern, providing theoretical basis for later metabolism. Therefore, the absorption and metabolism of ET or flavonoids after digestion in body and the upstream signaling pathway activating Nrf2/HO‐1, like PI3K or JNK phosphorylation, or downstream signaling pathway need further research. Abstract :